Pegolahan Jenis Sampah untuk Mengurangi Volume Sampah di Desa Asir-Asir Kecamatan Aceh Tengah - Ira Zulfa; Richasanty Septima; Eliyin Eliyin; Muhamad Yustisar (Jurnal Publikasi Manajemen Informatika, 2025)
In many areas, such as Asir-Asir Village, waste is a major problem. Analyzing the most common categories of waste and assessing waste management initiatives to reduce the amount of waste in the village were the objectives of this study. Data regarding waste composition, collection systems, and waste disposal were collected using survey, interview, and observation techniques. The results showed that most of the waste in Asir-Asir Village is organic waste. Waste segregation at source is one of the management initiatives that have been carried out, but organic waste processing still faces challenges. Based on these results, this study suggests several tactical steps to improve the effectiveness of waste management, including enhancing composting programs, creating waste banks, and encouraging social interaction to educate the community on the value of environmentally friendly waste management. As a result, it is expected that Asir-Asir Village will have a cleaner and healthier environment with less waste going to landfill.